The Effect of Survivin on Multidrug Resistance Mediated by P-Glycoprotein in MCF-7 and Its Adriamycin Resistant Cells - Liu, Feng; Xie, Zhen-Hua; Cai, Guo-Ping; Jiang, Yu-Yang (Biological & Pharmaceutical Bulletin, 2007)
Although anticancer chemotherapeutic drugs have been designed to inhibit the growth of tumor cells, chemotherapy frequently fails due to the development of multidrug resistance (MDR). In this paper, the effect of survivin on multidrug resistance mediated by P-glycoprotein (Pgp) was investigated in breast cancer cells. Overexpression of survivin in MCF-7 cells transfected with survivin expression vector pEGFP/survivin results in decreasing sensitivity to anticancer drugs and activation of Pgp to export drug out of cells. Down regulation of survivin in MCF-7/adriamycin (ADR) transfected with RNAi directed against survivin vector psh1/survivin could increase the drug accumulation in cells by inhibiting Pgp. Downregulation of the expression of the Pgp with the specific inhibitor verapamil could markedly suppress the survivin mRNA expression, whereas the reverse impact was not observed. Survivin might modulate the turnover of Pgp or transport by Pgp in cells, which result in anti-apoptosis and drug resistance. Our results suggest that survivin might play a key role in MDR in the presence of Pgp, and this might represent a novel strategy for modulating MDR in cancer cells.